(untitled) (Journal of Health Sciences, 2024)
Introduction: Aging is a natural, irreversible physiological process that depends on genetic, environmental, and lifestyle factors. Many physiological, biological, psychological, and other factors play a major role. According to the World Health Organization, falls are the second leading cause of unintentional injury death in the world and represent a major global public health problem. Falls are most commonly caused by intrinsic and extrinsic risk factors. A comprehensive assessment of fall risk is critical to the development of effective fall prevention programs. The screening protocol is brief, easy to use, and multifactorial and allows the identification of risk factors for falls. The aim of this study is to investigate the importance of the presence of risk factors in the home environment and the impact on increasing the risk of falls in people in the third age. Methods: The study was conducted in the municipality of Podgorica. 109 elderly people from urban and rural areas were included in the study using the snowball method. The instruments used in our study are a standardized checklist for assessing risk factors in the home environment, inside and outside the home (HASSAT), and a self-assessment scale of one’s own concern about a possible falls efficacy scale international. The survey was conducted from the end of October to the end of November 2023. Results: There is a statistically significant difference in social and physical activities of daily living in the area of concern about falling. When analyzing the overall result of the fear of falling scale in relation to gender, a significant statistical difference is found. The analysis of the individual rooms in relation to the age of the respondents shows that there is a significant statistical difference. Conclusion: The results obtained show that the high risk of falling is present in all rooms of the home environment for people in their 3rd year of life and that fear of falling increases with age.